Coping with stress - Packard, Gwen K. (New York : Rosen Pub. Group, 1997)
A discussion of why teenagers may face stress and what they can do about it, suggesting techniques for dealing with situations such as school difficulties, relationships, and natural disasters.
12 - 15 years
72013
Keywords: Stress in adolescence -- Juvenile literature; Stress management for teenagers -- Juvenile literature; Stress (Psychology)